THE PHILOSOPHICAL AND PEDAGOGICAL ORIGINS OF ACMEOLOGY DEVELOPMENT - Dyba, Tetiana H. (Educological discourse, 2015)
In the article the philosophical and pedagogical backgrounds of acmeology development beginning from the primitive communal system era, the ancient China, India and Antique world. The author summarized acmeologycal peaks of socio-cultural relationships of the ancient world; reviewed the scientific prerequisites of the acmeology developed by Apollodorus in 144 year B.C. in the Alexandrian philosophy school; the acme peaks have been analyzed on the bases of next three components of the outlook: mythological, religious and scientific. In the article beginnings of  XIV-XIX st. acmeology have been identified that include Renaissance epoch, Modern period, Age of Enlightenment and German idealism; also the acme-contribution of the famous scholars into backgrounds of acmeology formation in Russia.